2006
DOI: 10.1021/cm061122e
|View full text |Cite
|
Sign up to set email alerts
|

Direct Preparation and Patterning of Iron Oxide Nanoparticles via Microcontact Printing on Silicon Wafers for the Growth of Single-Walled Carbon Nanotubes

Abstract: Direct fabrication of uniform patterns of Fe 2 O 3 ‚xH 2 O nanoparticles on the SiO x /Si surface was achieved by microcontact printing (µCP). The as-prepared poly(dimethylsiloxane) (PDMS) stamps with a hydrophobic surface were used. The "ink" was an FeCl 3 ‚6H 2 O ethanol solution. Fe 2 O 3 ‚xH 2 O nanoparticles were formed on the stamps from the hydrolysis of FeCl 3 during the ink drying process and were then directly deposited onto the SiO x /Si surface with µCP. The nanoparticles were transferred to the ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 36 publications
0
38
0
Order By: Relevance
“…F i r s t , o r d e r e d c a t a l y s t s t ru c t u re s w e re e a s i l y a n d reproducibly patterned on quartz wafers by photolithography and PDMS stamp μCP techniques. Otherwise, FeCl 3 as the catalytic precursor is hard to uniformly pattern on the surface of wafers, especially for high concentrations of FeCl 3 [28]. Other catalysts such as ferritin [29,30], FeMo clusters [31], and Fe/Mo [32] nanoparticles also cannot be directly patterned on a wafer surface.…”
Section: Discussionmentioning
confidence: 99%
“…F i r s t , o r d e r e d c a t a l y s t s t ru c t u re s w e re e a s i l y a n d reproducibly patterned on quartz wafers by photolithography and PDMS stamp μCP techniques. Otherwise, FeCl 3 as the catalytic precursor is hard to uniformly pattern on the surface of wafers, especially for high concentrations of FeCl 3 [28]. Other catalysts such as ferritin [29,30], FeMo clusters [31], and Fe/Mo [32] nanoparticles also cannot be directly patterned on a wafer surface.…”
Section: Discussionmentioning
confidence: 99%
“…We found that PDMS stamps without ozone oxidization are very suitable to host both the formation and transfer of iron oxide nanoparticles of proper sizes onto substrates for CVD growth of SWNTs (Scheme 2). [18] An ethanol solution of FeCl 3 Á H 2 O can wet the as-prepared PDMS stamp very well. With the evaporation of ethanol, Fe 2 O 3 Á nH 2 O nanoparticles are formed from hydrolysis.…”
Section: Preparation and Deposition Of Catalyst Nanoparticles On Subsmentioning
confidence: 99%
“…Figure 1B shows the tapping-mode atomic force microscopy (AFM) image of the obtained Fe 2 O 3 Á nH 2 O nanoparticles on a SiO x /Si substrate. [18] Polystyrene (53 800)-block-poly(2-vinyl-pyridine) (8800) can form micelles with monodispersed size of $13.3 nm in toluene solution. Therefore, a fixed amount of FeCl 3 , which can be altered by using FeCl 3 aqueous solution of different concentration, can be loaded in the nanometer-sized water pools of the micelles.…”
Section: Preparation and Deposition Of Catalyst Nanoparticles On Subsmentioning
confidence: 99%
See 1 more Smart Citation
“…• C) rules out many substrates, not least flexible polymeric ones [4][5][6] which would allow subsequent ease of device production; in addition, the lateral size on which it is possible to grow such 'forests' of nanotubes by CVD is quite limited. Attempts at aligning nanotubes in composite systems using polymeric matrices have also often proven unsatisfactory.…”
Section: Introductionmentioning
confidence: 99%